Spiritual Strengthening of Man Through Prayer of Worship - Mohd Akib, Mohd Manawi; Mohd Ferdaus, Farah; Ishak, Hamdi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
There are both spiritual and physical aspects to every human being. Good spiritual health leads to good bodily health. In order to enjoy a long and prosperous life, these two parts must work together harmoniously. To have a healthy soul or spirituality means to have a strong spiritual component inside oneself. Due to its role as a centre of desires, the soul component is a driving force behind human bodily acts and behaviours. The purpose of this paper is to provide an explanation of the notion and significance of prayer in a Muslim’s quest to cultivate a positive character. Through research on book literacy, data were analysed using content analysis methodologies. The study's findings revealed that prayer is one of the elements in the Islamic psychotherapy method that corresponds with Iman psychotherapy, ‘Ibadah psychotherapy, and Tasawwuf psychotherapy. Psychospiritual therapy is one of the ways a Muslim can develop his consciousness as a servant while also serving as a reminder of Allah SWT’s limitless power and magnificence. A man might interact with Allah SWT as he prays and gain a sense of serenity in his spirit as a result.